Correlation of Personal Hygiene Knowledge, Attitude and Practices among School Children in Sumedang, Indonesia - Briska Sudjana; Irvan Afriandi; Julistio T. B. Djais (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: School-age children make up the largest proportion of Indonesian youth population. One of the ways to maintain children’s health is by making personal hygiene as a habit. The aim of this study was to analyze the correlation of personal hygiene knowledge, attitude and practices among school children. Methods: A cross-sectional analytic study, was carried out to 123 sixth graders at five elementary schools in Jatinangor , Sumedang, Indonesia, who were selected using a multi-stage sampling technique. This study was carried out in October 2013. A validated questionnaire was used to collect data of demographic characteristics of the subjects, knowledge, attitude and practice related to personal hygiene.The collected data was analyzed using Rank Spearman correlation with the level of significance was set at p< 0.05.Results: This study revealed that there was a significant correlation between knowledge and personal hygiene practice (p=0.016<0.05 and rs=0.358) and attitudes and personal hygiene practice (p=0.027<0.05 and rs=0.267).Conclusions: There is correlation of personal hygiene knowledge, attitudes and practices, however, the correlation is weak. [AMJ.2016;3(4):549–55]DOI: 10.15850/amj.v3n4.937